Assessment of turbulence and cavitation models in prediction of vortex induced cavitating flow in fuel injector nozzles. (December 2022) - He, Zhixia; Guan, Wei; Wang, Chuqiao; Guo, Genmiao; Zhang, Liang; Gavaises, Manolis
Highlights: RANS, LES and VLES model are used to assess predictive capabilities of string cavitation against experimental results. SS, ZGB, HEM and modified ZGB model adjusting self-adaptively condensation coefficient are conducted in simulations. The relationship of shear stress and strain rate is discussed to explain differences in model predictive ability. The effects of different models on flow discharge, velocity component field and phase transition field are analyzed. Abstract: Vortex-induced cavitation develops in high pressure fuel injector equipment in areas where despite the very high surrounding pressures (>100 MPa), the rotational motion of the fluid causes large pressure drops in the core of a well-organized longitudinal vortex structure leading to cavitation with normally string type correspondingly also called string cavitation ; typically, the size of the string cavitation is small compared to the overall dimensions while they develop in a transient mode linked with the local flow turbulence. To address these complex interaction processes, some turbulence models have been tested in a diesel injector nozzle for which quantitative experimental data are available and are utilized to assess the predictive capability of relevant models; the flow has been considered compressible, turbulent and isothermal. The closure models considered include the RNG k − ε, SST k − ω, RSM, WALE LES as well as a developed very-large eddy simulation model (VLES). The employed mass-transfer cavitation models are the Schnerr and Sauer (SS), Zwart-Gerber-Belamri (ZGB), HEM and a modified ZGB model with a self-adaptive adjustment of condensation coefficient. The results indicate that the RNG k − ε model and SST k − ω model fail to predict the string cavitation induced by vortex flow in the nozzle due to the drawback of the isotropic vortex-viscosity hypothesis. The RSM model could capture an acceptable string cavitation morphology. The numerical results utilizing the VLES model and LES model are in considerably good agreement with the experimental data, while the VLES model can provide the predictions of cavitating flow as precise as that using the LES model but on a much coarser mesh. The distributions of tangential velocity are similar to the velocity characteristics of Rankin vortex or Taylor vortex, which can help understand the coherent vortex structures in string cavitating flow. It is also shown that the RSM turbulence model with modified ZGB cavitation model improves the accuracy of prediction in the vortex-induced cavitation compared to the other three cavitation models.